2022
DOI: 10.11591/ijphs.v11i2.21375
|View full text |Cite
|
Sign up to set email alerts
|

Patient-perceived indicators as a basis for satisfaction assessment of healthcare

Abstract: Since satisfaction is a subjective matter, assessing satisfaction should begin from the individual perception of satisfaction. This study aimed to map the satisfaction indicators perceived by the patients as a foundation to develop instruments to assess health care satisfaction. The study adopted sequential exploratory design of mixed method approach. Thirty patients participated in the interviews and 300 patients for the survey. The thematic analysis identifies 159 items of satisfaction. The items were conden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…At the level of doctor-patient interaction, the behavior and attitude of healthcare professionals are important factors influencing patient satisfaction (42). Studies have found that patients often reduce uncertainty in treatment by certain social cues from the physician (e.g., tone of voice, temperament, mood) (37).…”
Section: Humanized Perceptionmentioning
confidence: 99%
“…At the level of doctor-patient interaction, the behavior and attitude of healthcare professionals are important factors influencing patient satisfaction (42). Studies have found that patients often reduce uncertainty in treatment by certain social cues from the physician (e.g., tone of voice, temperament, mood) (37).…”
Section: Humanized Perceptionmentioning
confidence: 99%
“…Patient satisfaction is a subjective matter because the standard of satisfaction for each individual is different. Even though there is no absolute value for the satisfaction variable, the definition of satisfaction must still be done to improve the quality of health services that can be accepted by all parties [27]. Quality of service has a significant influence on the level of patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%